2018
DOI: 10.1080/15384047.2018.1529099
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of TACE combined with apatinib on patients with advanced hepatocellular carcinoma: a retrospective study

Abstract: As a novel vascular endothelial growth factor receptor-2 tyrosine kinase inhibitor (VEGFR2-TKI), apatinib has a certain anti-tumor effect for a variety of solid tumors. The present study evaluates its efficacy and safety in advanced hepatocellular carcinoma (HCC). In this study, 47 patients with advanced HCC were included. TACE monotherapy group included 22 patients that responded to TACE, while the group that received TACE and apatinib included 25 patients that progressed on TACE and were able to receive apat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 31 publications
6
36
1
Order By: Relevance
“…On the other hand, the clinical study of sorafenib combined with TACE versus sorafenib alone in the treatment of progressive HCC showed that combination therapy can significantly improve tumor response rate and PFS, with reported median PFS of 5.2-5.4 months [6,16]. When treated with apatinib combined with TACE, several studies reported median PFS for advanced HCC of 4.5-9.5 months [10,19]. Our results showed a median PFS of up to 10 months.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…On the other hand, the clinical study of sorafenib combined with TACE versus sorafenib alone in the treatment of progressive HCC showed that combination therapy can significantly improve tumor response rate and PFS, with reported median PFS of 5.2-5.4 months [6,16]. When treated with apatinib combined with TACE, several studies reported median PFS for advanced HCC of 4.5-9.5 months [10,19]. Our results showed a median PFS of up to 10 months.…”
Section: Discussionsupporting
confidence: 47%
“…In contrast, although the combination of apatinib with TACE was compared with TACE alone, the median OS of the combined treatment group was reported to be 11.9-22 months [17][18][19][20][21]. This study showed that the median OS of 51 patients with advanced HCC was 15 months, which is in accordance with the previous reports [9][10][11]. On the other hand, the clinical study of sorafenib combined with TACE versus sorafenib alone in the treatment of progressive HCC showed that combination therapy can significantly improve tumor response rate and PFS, with reported median PFS of 5.2-5.4 months [6,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the limited indications and contraindications restrict the clinical use of the monotherapy which may lead to a high recurrence rate. In recent years, researchers have tried relevant clinical trials to seek the treatment effect of combined treatment on patients with intermediate-and advanced-stage HCC [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%